2022
DOI: 10.1186/s12877-022-02893-z
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality and cardiovascular events in a Spanish nonagenarian cohort according to type 2 diabetes mellitus status and established cardiovascular disease

Abstract: Background Despite the progressive aging of the population in industrialized countries, few studies have focused on the natural history of cardiovascular disease in the very old, and recommendations on prevention of cardiovascular disease in this population are lacking. We aimed to analyze all-cause mortality and cardiovascular events according to prevalent type 2 diabetes mellitus and established cardiovascular disease in nonagenarians from a Mediterranean population. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A potential non-linear relationship for continuous variables such as HbA1c will be accounted for by including splines in the model. In order to determine if T2D is a coronary risk equivalent among multimorbid older adults, we will compare the risk of CVD events and death of non-diabetic adults who had a previous CHD event to that of diabetic adults with no prior CHD [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential non-linear relationship for continuous variables such as HbA1c will be accounted for by including splines in the model. In order to determine if T2D is a coronary risk equivalent among multimorbid older adults, we will compare the risk of CVD events and death of non-diabetic adults who had a previous CHD event to that of diabetic adults with no prior CHD [12].…”
Section: Discussionmentioning
confidence: 99%
“…Two large contemporary studies found a lower risk of developing CHD in diabetics without prior CHD compared to non-diabetics with previous CHD [10, 11]. Yet, two studies that were conducted exclusively in older adults reported a similar risk of CVD across these two groups, supporting the status of diabetes as a coronary risk equivalent in this population [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…We have validated the quality of the EHRs in primary care for research use [19][20][21], and the database has been widely employed to study the epidemiology of cardiovascular risk factors in older patients [22].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, to resolve this limitation, the 2021 ESC guidelines on cardiovascular disease prevention in clinical practice, introduce the new SCORE2-OP to estimate 10 year risk of CVD death and CVD morbidity (nonfatal myocardial infarction, non-fatal stroke) for people between 70 and 89 years [11]. More speci cally, few studies have focused on the natural history of CVD in the very old population, since frail older people are usually excluded from randomized controlled trials [12][13][14].…”
Section: Introductionmentioning
confidence: 99%